2016
DOI: 10.1002/celc.201600082
|View full text |Cite
|
Sign up to set email alerts
|

Contrasts between Mild and Harsh Oxidation of Carbon Nanotubes in terms of their Properties and Electrochemical Performance

Abstract: Fundamental studies and electrochemical applications of carbon nanotubes (CNTs) have impacted a wide range of disciplines. A key issue for CNT electrochemistry is to understand how the physical, chemical, and electronic properties of different CNT materials affect their electrochemical performance. We investigate the differences arising from CNTs undergoing mild (H2O2) or harsh (HNO3) oxidation processes. Morphological assessment and chemical characterization of CNT materials revealed that HNO3 treatment (CNT–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 51 publications
1
6
0
Order By: Relevance
“…In our opinion, this indicates a change in surface chemistry or structure rather than a change in diffusion regime. It has been shown that HNO3-treatment of CNTs results in the increase of oxygen functional groups and induces defects that affect particularly the oxidation of AA [218]. Similar chemical and structural changes have been observed by Pumera et al after electrochemical oxidation of CNTs [219].…”
Section: Sensitive and Selective Detection Of Dopaminesupporting
confidence: 66%
“…In our opinion, this indicates a change in surface chemistry or structure rather than a change in diffusion regime. It has been shown that HNO3-treatment of CNTs results in the increase of oxygen functional groups and induces defects that affect particularly the oxidation of AA [218]. Similar chemical and structural changes have been observed by Pumera et al after electrochemical oxidation of CNTs [219].…”
Section: Sensitive and Selective Detection Of Dopaminesupporting
confidence: 66%
“…The C 1s HR-XPS spectra (Figures A and S4) showing a visible narrow peak and a small shoulder were deconvoluted in three peaks related to the following groups: sp 2 - (CC) and sp 3 -hybridized carbon (C–C) at 284.3 eV (Table S3); ,,,, alcohol and ether (C–OH, C–O–C) at around 285 eV (Table S3); ,,,, and carbonyl (CO, COOH) at around 288 eV (Table S3). ,,,, The two small peaks at 292.9 and 295.8 eV are attributed to K 2p, which is derived from the KOH solution employed during the electrochemical measurements and remained in the structure of GNR and GONR after electrochemical stabilization. For both GNR and GONR samples, there was an increase in the percentage content of C bonded to O (oxidation of C–C or CC bonds) and a displacement of the peak position of C (bonded to O) to lower energy (Table S3) after electrochemical stabilization.…”
Section: Resultsmentioning
confidence: 99%
“…Studies published in the literature have reported the involvement of N, C, ,, and/or O ,,, groups (and their respective amounts) in ORR. A number of studies have also pointed out the acidic ,,,, or alkaline , medium used during the electrochemical measurements. ,,, Some works have also focused their study toward investigating the defects and edges ,,,, , ,,,,, present on the nanostructured surfaces of metal-free carbon materials.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, oxidation is known for ruthless deterioration of CNTs' unique structure making it a perfect model for our considerations. 19,20 Functionalisation degree, i.e. population of oxygen containing groups was determined both by means of thermogravimetric analysis and modied Boehm titration protocol (ESI †) and it was 4.2 mmol g À1 (both COOH and OH) ( Fig.…”
Section: Resultsmentioning
confidence: 99%